Applying Fact Reason Elaboration Shift (FRESH) Technique to Develope Writing Skill of SMAN Model Terpadu Madani - Yanti Permatasari; Abdul Kamaruddin; Afrillia Anggreni; Nur Sehang Thamrin (Universitas Cokroaminoto Palopo, 2024)
The aims of this research is to find out whether or not the Applying Fact Reason Elaboration Shift (FRESH) Technique can develope the student’s skill to write descriptive text. This research applied a quasi-experimental research design that involved experimental group and control group. The sample of this research was 48 student’s, which were divided into 26 students of class Xl E as the experimental group and 22 student’s of class XI D as the control group. The sample was selected by using clusters technique. The data was collected by administering a writing test consisting of a pre-test and post-test. Then the treatment was only given to the experimental group. The result of the pre-test shows that the mean score of the experimental group is 29.8 while the mean score of the control group is 40.8. This demonstrated that the pre-test mean score of the experimental group were lower compared to the control group. After conducting the treatment, the result of the post-test shows that the mean score of the experimental group is 75.13 while the mean score of the control group is 65.5. It indicates that the experimental group has shown improvement in their writing skill compared to the control group. By applying 46 degree of freedom (df) and 0.05 level of significance, it can be seen that the (3.76) is higher than the (2.021). It means that the research hypothesis is accepted. In conclusion, that the Applying Fact Reason Elaboration Shift (FRESH) Technique can develope the student’s writing skill to the elevent grade of SMAN Model Terpadu Madani